Sustainable urban growth scenario for climate-vulnerable coastal cities: An analysis based on ubiquitous big data and a hybrid fuzzy-cellular automata - Mehdi Azari; Sina Sadeghfam; Seyed Mostafa Hedayatnezhad Kashi (Land Use Policy, 2026)

Introducing thermal sensitivity to devegetation using an AI-based framework for capturing urbanization stress - Ghadah Hasan Mohamed; Fatima Asaad Tayeb; Mehdi Azari; Sina Sadeghfam (International Journal of Remote Sensing, 2026)

Characteristics of Microplastics in a Hospital Wastewater Treatment Plant Effluent and Hazard Risk Assessment - Hossein Kamani; Mehdi Ghayebzadeh; Ali Azari; Fatemeh Ganji (Environmental Processes, 2024)

Correction: characterization of vaginal lactobacillus species as a predictor of fertility among iranian women with unexplained recurrent miscarriage and fertile women without miscarriage history using machine learning modeling - Farkhondeh Pouresmaeili; Saeideh Alidoost; Masoumeh Azimirad; Mehdi Azizmohammad Looha; Armitasadat Emami Meibodi; Atieh Abedin-Do; Hourieh Shamshiri; Mahan Mohammadi; Iman Azari; Zahra Fazeli; Abbas Yadegar; Tayebeh S. Hosseinpour (Molecular Biology Reports, 2023)

Characterization of vaginal Lactobacillus species as a predictor of fertility among Iranian women with unexplained recurrent miscarriage and fertile women without miscarriage history using machine learning modeling - Farkhondeh Pouresmaeili; Saeideh Alidoost; Masoumeh Azimirad; Mehdi Azizmohammad Looha; Armitasadat Emami Meibodi; Atieh Abedin-Do; Hourieh Shamshiri; Mahan Mohammadi; Iman Azari; Zahra Fazeli; Abbas Yadegar; Tayebeh S. Hosseinpour (Molecular Biology Reports, 2023)

A GIS-based approach for accident hotspots mapping in mountain roads using seasonal and geometric indicators - Mehdi Azari; Ali Paydar; Bakhtiar Feizizadeh; Vahid Gara Hasanlou (Applied Geomatics, 2023)

Synergistic effects of sodium butyrate and sodium propionate on the growth performance, blood biochemistry, immunity, and immune-related gene expression of goldfish (Carassius auratus) - Mehdi Shamsaie Mehrgan; Seyed Pezhman Hosseini Shekarabi; Azin Azari; Sevdan Yilmaz; Christian Lückstädt; Houman Rajabi Islami (Aquaculture International, 2022)

Using log analytics and process mining to enable self-healing in the Internet of Things - Prasannjeet Singh; Mehdi Saman Azari; Francesco Vitale; Francesco Flammini; Nicola Mazzocca; Mauro Caporuscio; Johan Thornadtsson (Environment Systems and Decisions, 2022)
The Internet of Things (IoT) is rapidly developing in diverse and critical applications such as environmental sensing and industrial control systems. IoT devices can be very heterogeneous in terms of hardware and software architectures, communication protocols, and/or manufacturers. Therefore, when those devices are connected together to build a complex system, detecting and fixing any anomalies can be very challenging. In this paper, we explore a relatively novel technique known as Process Mining, which—in combination with log-file analytics and machine learning—can support early diagnosis, prognosis, and subsequent automated repair to improve the resilience of IoT devices within possibly complex cyber-physical systems. Issues addressed in this paper include generation of consistent Event Logs and definition of a roadmap toward effective Process Discovery and Conformance Checking to support Self-Healing in IoT.

Decellularization of kidney tissue: comparison of sodium lauryl ether sulfate and sodium dodecyl sulfate for allotransplantation in rat - Mohammad Amin Keshvari; Alireza Afshar; Sajad Daneshi; Arezoo Khoradmehr; Mandana Baghban; Mahdi Muhaddesi; Pouya Behrouzi; Mohammad Reza Miri; Hossein Azari; Iraj Nabipour; Reza Shirazi; Mehdi Mahmudpour; et al. (Cell and Tissue Research, 2021)

Responses of surface water quality to future land cover and climate changes in the Neka River basin, Northern Iran - Sharif Joorabian Shooshtari; Kamran Shayesteh; Mehdi Gholamalifard; Mahmood Azari; Juan Ignacio López-Moreno (Environmental Monitoring and Assessment, 2021)

Green preparation of activated carbon from pomegranate peel coated with zero-valent iron nanoparticles (nZVI) and isotherm and kinetic studies of amoxicillin removal in water - Imran Ali; Shirin Afshinb; Yousef Poureshgh; Ali Azari; Yousef Rashtbari; Abolfazl Feizizadeh; Asghar Hamzezadeh; Mehdi Fazlzadeh (Environmental Science and Pollution Research, 2020)

Simulating Unsaturated Zone of Soil for Estimating the Recharge Rate and Flow Exchange Between a River and an Aquifer - Masoomeh Zeinali; Arash Azari; Mohammad Mehdi Heidari (Water Resources Management, 2020)

Impacts of future land cover and climate change on the water balance in northern Iran - Sharif Joorabian Shooshtari; Kamran Shayesteh; Mehdi Gholamalifard; Mahmood Azari; Roberto Serrano-Notivoli; Juan Ignacio López-Moreno (Hydrological Sciences Journal, 2017)

Oocyte maturation, embryo development and gene expression following two different methods of bovine cumulus-oocyte complexes vitrification - Mehdi Azari; Mojtaba Kafi; Bita Ebrahimi; Roya Fatehi; Mahboobeh Jamalzadeh (Veterinary Research Communications, 2017)

Interference of Human Impacts in Urban Growth Modelling with Transition Rules of Cellular Automata, GIS and Multi-Temporal Satellite Imagery: A Case Study of Maraghe, Iran - Mehdi Azari; Mohsen Ahadnejad Reveshty (Journal of the Indian Society of Remote Sensing, 2013)